The Application of Multimedia-Based Presentation in Improving Students’ Speaking Skill - Fauzi, Imam (University of Muhammadiyah Prof. DR. HAMKA, 2016)
Although speaking is one the important skills, it is not easy to have this skill. English teachers have used various techniques to improve students’ speaking skill. So far, however, there has been little discussion about the role of multimedia-based presentation in improving students’ speaking skill. This action research taking place at a private university in Serang, Banten investigated the use of multimedia-based presentation to improve speaking skill. The findings showed that students’ speaking and presentation skills improved and their confidence to speak in front of the class increased. Students also learned technology which is beneficial for their study and future career. This study, therefore, suggests that teachers consider this aid in teaching-learning processes.